PERTANGGUNGJAWABAN PIDANA APARAT PENEGAK HUKUM ATAS PENUNDAAN PROSES PERADILAN KASUS KORUPSI PT KRAKATAU STEEL - Norma Risca Pratiwi; Ridwan Ridwan; Reine Rofiana (Faculty of Law, Khairun University, 2024)
In the process of examining the PT Krakatau Steel corruption criminal case, there was a neglect of legal obligations by law enforcement officials regarding the fulfillment of the defendant's rights. The main problem studied in this research is how the process of delays in the criminal justice process for criminal acts of corruption in the PT Krakatau Steel case and what forms of criminal responsibility there are for law enforcement officials for delays in the criminal justice process for criminal acts of corruption in the case of PT Krakatau Steel (Legal Study of District Court Decisions Attack). This research was conducted using normative juridical methods. The results of this research show that in the process of examining the criminal corruption case in the PT Krakatau Steel case, during the evidentiary process at trial, which is part of the prosecution stage in the criminal justice process, there were often delays of up to 7 times by the prosecutor and substitute ad hoc judge. The form of criminal responsibility for law enforcement officials for delays in the criminal justice process for the criminal act of corruption in the PT Krakatau Steel case is the prosecutor and substitute ad hoc judge for their actions in delaying the trial by not obeying statutory orders by officials as a form of contempt of justice (contempt). of court). So that the substitute ad hoc prosecutor and judge can be held criminally responsible under Article 216 paragraph (1) of the Criminal Code concerning Crimes Against Public Authorities.